Peranan Media Animasi terhadap Peningkatan Penguasaan Konsep Mahasiswa PGSD - Fazakkir Noor (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This research aims to know applying of animation media to increase students mastery of concept in learning process on circulation system of human blood at PGSD students S-1 FKIP UMP. Research method used in this observation ’queasy experiment’, the collection of data collected use quistioners and analized with t test by doing pre-test post-test, with design 0₁ X 0₂. Research population all students room B-32 which amount 35 students and all population become sample. Validity of 20 items tested is tall and rebiliaty is reliable, and normality test of data distribution is normal, while homoginity variant result and post test shows F count = 1,71< F table 7,47, While result pre test and post test show t count 13,69 >t table 2,04, it means any significant difference. The result of pre-test level indicator C1, C2, C3 and C4 less tall, and post-test level is taller. Thus, it can be concluded that learning process used media of animation can increase students’ mastery of concept.